2007
DOI: 10.1038/nchembio869
|View full text |Cite
|
Sign up to set email alerts
|

Genomics-driven discovery of PKS-NRPS hybrid metabolites from Aspergillus nidulans

Abstract: In the postgenomic era it has become increasingly apparent that the vast number of predicted biosynthesis genes of microorganisms is not reflected by the metabolic profile observed under standard fermentation conditions. In the absence of a particular (in most cases unknown) trigger these gene loci remain silent. Because these cryptic gene clusters may code for the biosynthesis of important virulence factors, toxins, or even drug candidates, new strategies for their activation are urgently needed to make use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
476
0
8

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 537 publications
(490 citation statements)
references
References 34 publications
6
476
0
8
Order By: Relevance
“…Recent data further complicate a serious estimation because communication occurs between gene clusters, which could potentially lead to even more compounds (5). A major hurdle to identifying this untapped reservoir, however, is the observation that most of these gene clusters are silent under standard laboratory conditions (6)(7)(8). To address this problem, methods were established to activate silent gene clusters by genetic engineering (6,7,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data further complicate a serious estimation because communication occurs between gene clusters, which could potentially lead to even more compounds (5). A major hurdle to identifying this untapped reservoir, however, is the observation that most of these gene clusters are silent under standard laboratory conditions (6)(7)(8). To address this problem, methods were established to activate silent gene clusters by genetic engineering (6,7,9).…”
mentioning
confidence: 99%
“…A major hurdle to identifying this untapped reservoir, however, is the observation that most of these gene clusters are silent under standard laboratory conditions (6)(7)(8). To address this problem, methods were established to activate silent gene clusters by genetic engineering (6,7,9). The most challenging question, however, is the identification of the true function of these compounds in the habitat.…”
mentioning
confidence: 99%
“…9,10,21−23 While the biosynthesis of these compounds is likely to be related, 24,25 their synthesis required at least 14 steps. 22 From a very limited structure−activity relationship study (SAR), we learned that the much simpler L-tyrosinol-propionamide 4 was able to induce neuronal differentiation, albeit at higher concentration than the parent analog 3.…”
mentioning
confidence: 99%
“…To gain access to this untapped reservoir of potentially bioactive natural products, various strategies to induce the expression of silent genes have been developed. 4,7 Important recent examples involve the ectopic expression of a regulatory gene, 8 the induction of a transcription activator by promotor exchange, 9 as well as modulation of the epigenetic regulation of biosynthetic genes at the chromatin level. [10][11][12][13] Furthermore, it was shown that the intimate contact between A. nidulans and a soil-dwelling actinomycete may lead to the specific induction of a cryptic polyketide gene cluster.…”
mentioning
confidence: 99%